EXPLORING STUDENTS' VIEWS ON THE USE OF E-PORTFOLIO AS A SPEAKING LEARNING TOOL IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM - Pamastu Narpaduita; Bambang Widi Pratolo (IKIP Siliwangi, 2024)
E-portfolios offer diverse benefits for assessment and learning, extensively used in basic to tertiary education, including universities. However, e-portfolios have not been widely implemented in speaking classes. This study aimed to explore students' views towards the use of e-portfolios as a learning tool in English as a Foreign Language (EFL) classrooms, particularly in speaking classes at university levels. This study used descriptive qualitative research. The research was conducted in an English education program at a private university in Yogyakarta that has integrated e-portfolio as a speaking learning tool. Data collection involved semi-structured interviews. The analysis followed a coding process by Weston. The results indicated overwhelmingly positive student responses to e-portfolios in EFL speaking classes, citing them as interesting tools, aiding speaking learning progress monitoring, improving their creativity, enhancing self-management abilities, fostering their motivation through feedback and reflection, serving as a lifelong learning tool, and being effective and efficient. The study suggests implications for online and blended learning, emphasizing the importance of technological proficiency. Integrating e-portfolios aligns with the digital era and offers lifelong learning benefits. It also encourages ELT teachers, students, and researchers to further explore e-portfolios as a valuable topic for future research.